Analisis Penerapan Asas Lex Favor Reo dalam Perkara Tindak Pidana Pembunuhan dengan Pemberatan (Studi Putusan Nomor 213/Pid.B/2025/Pli) - Cahaya Mutiara; Mangaraja Manurung (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
During the transition period from the Criminal Code (WvS) to Law Number 1 of 2023 concerning the Criminal Code, the application of the lex favor reo principle has become an important issue. The problem of this research is how legal provisions govern the crime of aggravated murder in Indonesia and the legal considerations of the panel of judges in applying the lex favor reo principle. The purpose of this research is to analyze legal regulations regarding aggravated murder in the Criminal Code (WvS) and the new Criminal Code, as well as the legal factors considered by judges when applying this principle. The research method used is normative legal research with statutory, case, contextual, and comparative approaches. Primary, secondary, and tertiary legal sources were obtained through library research and analyzed qualitatively. The results indicate that the provisions regarding aggravated murder are contained in Article 339 of the Criminal Code (WvS) and Article 458 paragraph (3) of Law Number 1 of 2023 concerning the Criminal Code. These provisions essentially have the same substance, regulating murder preceded, accompanied, or followed by another crime for a specific purpose. The new Criminal Code has more modern sentencing guidelines and practices. In Decision Number 213/Pid.B/2025/PN Pli, the panel of judges applied Article 458 paragraph (3) of the new Criminal Code based on the lex favor reo principle because it was considered more advantageous to the defendant in achieving justice, legal certainty, and protecting the defendant's rights during the transitional period of criminal law.